Meat Quality Parameters and Sensory Properties of One High-Performing and Two Local Chicken Breeds Fed with Vicia faba - Cynthia I. Escobedo del Bosque; Brianne A. Altmann; Marco Ciulu; Ingrid Halle; Simon Jansen; Tanja Nolte; Steffen Weigend; Daniel Mörlein (Foods, 2020)
The current practices of the poultry industry have raised concerns among consumers. Among these is the culling of day-old male chicks of laying hybrids; a suitable alternative for this could be the use of dual-purpose breeds where both sexes are used. Another practice that causes concern is the import of large quantities of soybeans for feedstuff production. Substitutes for these soybean-based products are regional protein crops, such as faba beans (Vicia faba L.; FBs). The objective of this study was to test the suitability of FB as a locally produced soybean meal replacement for two local dual-purpose chicken breeds and one high-performing layer line. The breast and leg meat of male Bresse Gauloise (BG), Vorwerkhuhn (VH), and White Rock (WR) animals was evaluated for different meat quality parameters: pH, color, water holding capacity, and tenderness. Sensory properties of the samples were evaluated by a trained panel with a conventional descriptive analysis. Results show different effects of FB diets on meat quality parameters in the different breeds. The attributes mostly affected by the diet are related to aroma, flavor, and texture, particularly in VH and WR. Overall, faba beans appear to be an acceptable dietary protein source for rearing these breeds for meat production.